2004
DOI: 10.1152/ajplung.00177.2003
|View full text |Cite
|
Sign up to set email alerts
|

H2O2inhibits alveolar epithelial wound repair in vitro by induction of apoptosis

Abstract: Reactive oxygen species (ROS) are released into the alveolar space and contribute to alveolar epithelial damage in patients with acute lung injury. However, the role of ROS in alveolar repair is not known. We studied the effect of ROS in our in vitro wound healing model using either human A549 alveolar epithelial cells or primary distal lung epithelial cells. We found that H(2)O(2) inhibited alveolar epithelial repair in a concentration-dependent manner. At similar concentrations, H(2)O(2) also induced apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 26 publications
(37 reference statements)
1
48
0
1
Order By: Relevance
“…Reactive oxygen species (ROS) are released into the alveolar space and contribute to alveolar epithelial damage in patients with acute lung injury. It was shown that H 2 O 2 inhibits alveolar epithelial wound repair in large part by induction of apoptosis and that apoptosis inhibition can maintain wound repair and cell viability in the face of ROS (24). Consistent with this assumption, KGF inhibited H 2 O 2 -induced cleavage of both procaspase-3 and the substrate of caspase-3, the poly(ADP-ribose) polymerase protein, in murine lung cells (42).…”
mentioning
confidence: 60%
“…Reactive oxygen species (ROS) are released into the alveolar space and contribute to alveolar epithelial damage in patients with acute lung injury. It was shown that H 2 O 2 inhibits alveolar epithelial wound repair in large part by induction of apoptosis and that apoptosis inhibition can maintain wound repair and cell viability in the face of ROS (24). Consistent with this assumption, KGF inhibited H 2 O 2 -induced cleavage of both procaspase-3 and the substrate of caspase-3, the poly(ADP-ribose) polymerase protein, in murine lung cells (42).…”
mentioning
confidence: 60%
“…An in vitro epithelial injury model that allows for the study of epithelial repair processes in the lung was adapted for use in this study (16)(17)(18). Briefly, at 0 hours on the timeline in Figure 1, epithelia were scraped in two perpendicular lines with a p1000 pipette tip and placed in bromodeoxyuridine (BrdU)-containing (10 mM) medium.…”
Section: Mechanical Injury Modelmentioning
confidence: 99%
“…may signal to more distant surviving cells via calcium waves or paracrine mediators, as has been previously demonstrated (4,58), responses that could effectuate repair. As the CCN proteins are known to regulate apoptosis (41,63), an additional mechanism by which they might regulate wound repair is via decreased apoptosis of epithelial cells at the wound edge, an established mechanism for differential wound repair (20). Although neutrophil transmigration induces epithelial cell death and denudation of the epithelium in our models, the stimuli used (1 M fMLP in vitro or 1 g KC in vivo) are relatively modest, and the injury induced is relatively mild and repairs rapidly.…”
Section: Discussionmentioning
confidence: 99%